Thermal, structural and optical properties of tungsten-fluorophosphate glasses and glass-ceramics with high lead fluoride contents - Rachel Prado Russo Delorenzo Nardi; Raphael Rodrigues Faleiros; Andrea Simone Stucchi De Camargo; Sidney José Lima Ribeiro; Camila Pereira; Lia Mara Marcondes; Gislene Batista; Fábia Castro Cassanjes; Gael Poirier (Optical Materials: X, 2023)
Eu3+-doped lead fluorophosphate glass samples were prepared in the ternary system (40-x)NaPO3-xWO3-60PbF2 by the melt-quenching method. The influence of the NaPO3/WO3 ratio on the thermal and structural properties as well as on the ability of these compositions to crystallize as glass-ceramics containing lead fluoride phase β-PbF2 was investigated. Thermal properties and characteristic temperatures were determined by DSC and used to define suitable heat-treatment temperatures for selective crystallization. The corresponding crystalline phases and average crystallite sizes were determined by X-ray diffraction. Structural changes versus composition were also studied by Raman spectroscopy. UV-visible absorption spectra were used to determine the bandgap energies versus composition. Specific compositions exhibiting β-PbF2 crystallization were selected and Eu3+ emission spectra were used to check the Eu3+ environment and crystallization state as a function of heat-treatment conditions and glass composition. The results suggest that progressive β-PbF2 crystallization promotes a higher symmetry and lower phonon energy environment of Eu3+ resulting in longer excited state lifetimes only for WO3 richer compositions.